People living alone with dementia: Ethical guidelines for social research: Long‐term care and ethics. (7th December 2020) - de Medeiros, Kate; Girling, Laura
Abstract: Background: Although it is believed that around 1/3 of people with Alzheimer's and related dementias (ADRD) live alone in the community, the actual percentage is likely higher given dementias are often underdiagnosed and underreported. In addition, significant barriers (e.g., compromised capacity, accessibility issues, stigmatization) to the research inclusion of those residing alone with ADRD has led this population to be overlooked and/or deliberately excluded from social inquiry. Research systems that pose insurmountable barriers to the inclusion of vulnerable populations with ADRD prevent evidenced‐based knowledge that could constructively benefit future patients and caregivers. The present study was designed to create an important evidence base for ethical considerations regarding inclusion and exclusion of people living alone with ADRD into social research. Method: Funded by the National Institute on Aging, the present study conducted a comprehensive narrative synthesis of published ADRD and gray literature and 10 in‐depth interviews with key gatekeepers (e.g., people who can provide or deny access to people living alone with ADRD) to develop data‐driven recommendations to support the research inclusion of people living alone with ADRD. Result: The combined narrative synthesis and primary data collection underscored three areas of inclusionary/exclusionary concern: 1) fluctuating capacity to give informed consent, 2) absence of study partners or surrogate decisions‐makers and 3) social and environmental barriers exacerbating disparities by discouraging inclusion of a severely marginalized population. Detailed guidelines will be discussed in each of these three areas. Conclusion: The developed guidelines provide significant insights into how the dementia research community can overcome barriers to research‐driven learning in order to ethically incorporate live‐alone people with dementia into social science explorations, providing direction for current and future research.